Early Cartesianism and the Journal des Sçavans, 1665–1671 - Dobre, Mihnea (Studium, 2012)
The appearance of scientific journals in the second half of the seventeenth century not only presented new opportunities for the dissemination of knowledge, but also offers the historian a privileged view of the shared knowledge within the scientific community. The Journal des Sçavans, founded in 1665, proclaimed its ambition to disseminate news about books and people concerning the République des lettres. Given the reportedly high interest in and opposition to the rise of Cartesianism among contemporary philosophers, this paper explores the discussion of Cartesianism within the pages of the Journal. It is shown that debates on Cartesianism formed only a small portion of the articles in the Journal. Although the majority of commentaries referred to the metaphysical foundations of Cartesian philosophy, a considerable number of instances were found referring to empirical tests of the theory. Finally, as the Journal does not mention the condemnations or censorship of Cartesianism, we cannot speak of a general feeling of hostility against Cartesian philosophers among the editors or intended audience of the Journal.